Health Seeking Behavior Among Adults and Elderly With Chronic Health Condition(s) in Albania - Gabrani, Jonila; Schindler, Christian; Wyss, Kaspar (Frontiers in Public Health, 2021)
Aim: Assess the use of different health care service providers by adults (aged 18-59) and elderly (aged >=60) who suffer from non-communicable disease (NCD) and explore relationships between sociodemographic variables and care-seeking behaviors. Methods: A cross-sectional survey was conducted in the districts of Diber and Fier in December 2018, using random cluster sampling. Descriptive statistics were used to compare the care-seeking behaviors of adults and elderly people. We employed binary and multinomial logistic regression to assess factors associated with the type of health service provider used. Analyses were adjusted for clustering within districts of residence. Results: Out of 3,799 respondents, 1,116 (29.4%) suffered from an NCD. Of these, 95% sought to obtain care for their chronic condition through public healthcare providers. The elderly were more likely to use primary healthcare services (PHC) to initiate care when facing health problems (56%), compared to those aged 18 to 65 years (49%, p< 0,001). Over the last 8 weeks, 82% (914/1116) of participants sought care. Binary and multinomial logistic regression analyses, adjusted for socio-demographic variables, showed that the elderly were more likely to choose PHC services ( OR 1.56; 95% CI:1.04; 2.35). Moreover, individuals who suffered from hypertension used PHC services more frequently than hospitals (OR 1.94; 95% CI: 1.32; 2.85). A positive association was found between living in an urban area and seeking care for NCDs at polyclinics (OR 10.1; 95% CI: 2.1; 50.1). There was no significant gender difference observed with regard to the type of provider consulted. Conclusion: Public facilities were reported as the main providers for initiating care and the main providers used in the 8 weeks prior to the interview. While a majority of elderly people visited a PHC to initiate treatment (and follow up) on their chronic conditions, a substantial proportion of adults (aged 18-59) initiated and sought regular NCD care at a hospital. Educating patients and caregivers on active participation in NCD prevention, management and control through the PHC level should be a long-term effort, along with the establishment of well-structured referral mechanisms and integrated care systems.